The nature of the State and its relationship with civil society in the face of the Covid-19 crises (Research, Society and Development, 2021)
With the Covid-19 pandemic comes a reflection on the role of the State and its relationship with civil society. Thus, it is essential to discuss the role of the Brazilian State in combating the health crisis in question. This article discusses the concept of State and Civil Society together with a reflection on the role of the State in the pandemic scenario, the importance of civil society and the obstacles and challenges both from a state and social point of view. Therefore, the deductive approach was adopted as a method of approach to understand the importance of income transfer programs, in addition to revealing the nature of the State and its social impacts, especially with regard to the low-income population. However, the study presented reveals the importance and absence of a national plan to combat the pandemic, as well as a medium and long-term study on the need for financial assistance for the population in a situation of social vulnerability.